1993
DOI: 10.1136/bmj.306.6876.484
|View full text |Cite
|
Sign up to set email alerts
|

Fat and female fecundity: prospective study of effect of body fat distribution on conception rates.

Abstract: Objectives-To study the effect of body fat distribution in women ofreproductive age on fecundity.Design-Prospective cohort study of all women who had entered a donor insemination programme.Setting-One fertility clinic serving a large part of the midwest ofthe Netherlands.Subjects-Of 542 women attending the clinic for artificial insemination for the first time, 500 women were eligible for study.Main outcome measures-Probability of conception per cycle and number of insemination cycles before pregnancy or stoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
266
1
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(278 citation statements)
references
References 14 publications
6
266
1
5
Order By: Relevance
“…Besides, high body fat mass is also associated with infertility. 8 Therefore, we consider a change in fat metabolism during the first pregnancy to be a more likely explanation. Indeed, the first pregnancy is unique.…”
Section: First Pregnancy and Fat Deposition H Friis Et Almentioning
confidence: 99%
“…Besides, high body fat mass is also associated with infertility. 8 Therefore, we consider a change in fat metabolism during the first pregnancy to be a more likely explanation. Indeed, the first pregnancy is unique.…”
Section: First Pregnancy and Fat Deposition H Friis Et Almentioning
confidence: 99%
“…34 Also, in a Dutch prospective study on arti®cial insemination, a 0.1 unit increase in WHR led to a 30% decrease in probability of conception, after controlling for many interfering variables. 35 The conclusion from Singh's studies on Western populations is that body fat and its distribution plays a crucial role in judgements of female attractiveness, health, youthfulness, and reproductive potential. The suggestion is not that shape as evinced by WHR is the only factor in mate selection but one involved in the initial stages,`a ®rst wide pass ®lter'.…”
Section: Fertilitymentioning
confidence: 99%
“…8) and infertility in women. 9,10 It has been suggested that a WHR exceeding certain cut-off points (0.95 for men and 0.80 for women) implies an increased cardiovascular health risk. 11 The abdominal fatness appears to increase with age among both genders.…”
Section: Introductionmentioning
confidence: 99%